2017
DOI: 10.4046/trd.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Pneumonia in Hospitalized Patients with Seasonal Influenza A or B

Abstract: BackgroundMost patients with influenza recover spontaneously or following treatment with an anti-viral agent, but some patients experience pneumonia requiring hospitalization. We conducted a retrospective review to determine the incidence and risk factors of pneumonia in hospitalized patients with influenza A or B.MethodsA total of 213 patients aged 18 years or older and hospitalized with influenza between January 2012 and January 2015 were included in this study. A reverse-transcriptase polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the Simmerman et al 12 study, it was shown that older patients or those with certain underlying diseases are more likely to develop pneumonia among hospitalized patients. According to the Chu et al 13 study, the incidence of pneumonia after influenza infection in hospitalized patients was 65.7%. Risk factors for the development of pneumonia were identified by age, respiratory disease, and underlying disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Simmerman et al 12 study, it was shown that older patients or those with certain underlying diseases are more likely to develop pneumonia among hospitalized patients. According to the Chu et al 13 study, the incidence of pneumonia after influenza infection in hospitalized patients was 65.7%. Risk factors for the development of pneumonia were identified by age, respiratory disease, and underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for the development of pneumonia were identified by age, respiratory disease, and underlying disease. 13 14 When investigating factors affecting incidence of pneumonia after influenza infection, the result from our study using the claims data included age, preceding chronic diseases, and underlying diseases. It was similar to that from previous studies using medical records of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…While chronic diseases have been reported as risk factors for serious complications in influenza [ 2 , 16 ], such factors for pneumonia are not yet fully established. Even though several hospital-based studies have identified chronic respiratory disease and older age as relevant risk factors for pneumonia [ 14 , 28 ], it remains unclear whether these risk factors are applicable to general populations because of the potential selection bias in those studies; specifically, patients admitted for influenza symptoms would be more likely to be already critically ill at the time of admission or to have a serious underlying disease. Our large-scale population-based study also determined that older age and chronic respiratory disease were independent risk factors for pneumonia, in addition to male gender, dementia, congestive heart failure, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It also emphasizes the importance of gathering any history relative to any preceding upper respiratory viral illness when suspecting pneumonia. The incidence of subsequent pneumonia in hospitalized patients has been shown to be 68.6% and 56.9%, respectively, for influenza types A and B [ 8 ]. Treatment with Oseltamivir alone has not been noted to prevent the development of SOP [ 9 ].…”
Section: Discussionmentioning
confidence: 99%